SOCIAL MEDIA AND INTERCULTURAL COMMUNICATION - Tkachuk, Arsen (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The article analyzes the role of social media in fostering intercultural communication, which has become particularly relevant amid globalization and increasing population migration. Social media alters how people from different cultural backgrounds interact and creates new opportunities for sharing information, cultural values, and experiences. This study aims to assess social media's impact on intercultural adaptation and social network formation and identify the advantages and disadvantages of its use in intercultural communication. The research objectives include analyzing how social media helps reduce cultural barriers and stereotypes, shape identity, and promote mutual understanding. Research methods include qualitative content analysis, user surveys, and case studies of successful intercultural interactions through social media. The study results indicate that active use of social media positively affects intercultural adaptation, enabling new social connections and networks. Participants highlighted the importance of social media in fostering a sense of belonging to a community, which, in turn, enhances intercultural communication. The study's findings have significant practical implications. They can be applied in developing support programs for intercultural adaptation and optimizing communication strategies in educational and social domains. The study also points towards future research perspectives, including examining the specific use of social media across different cultures and exploring the impact of emerging technologies on intercultural communication within the context of rapid social changes.